Algoritmos evolutivos many objectives aplicados ao problema de roteamento Multicast com qualidade de serviço - Lafetá, Thiago Fialho de Queiroz (2016)
In computer networks, to ensure that an adequate level of communication end-to-end is achieved, it is important to ensure a routing with quality of service (QoS). The routing problem with QoS involves multiple objectives to be optimized or serviced simultaneously. When this multicast routing is the kind which involves multiple recipients, the complexity of the problem is even greater. Previous studies investigating the use of evolutionary algorithms Multiobjetivos (AEMO) in multicast routing problem with QoS. It is known that the greater the number of objects to be optimized, the more complex becomes the multiobjective and more difficult problem becomes convergence AEMOs Traditional. Therefore, the use of an evolutionary method many objective is proposed: the AEMMT (Evolutionary Algorithm with Multiobjective Many tables). The AEMMT was specially developed for problems with a large number of objectives and expected it to behave more appropriately with the increasing number of objectives in the multicast routing with QoS. In order to strengthen the convergence this paper proposes a new many objective based on the strategies of AEMMT appointed AEMMD.